A representação social da violência de gênero contra a mulher no Espírito Santo - Natale, Raquelli (2015)
The main objective of this study is to analyze how the media help to build the social representation of gender violence the Espírito Santo, the state that leads the national ranking of femicide, with 9.8 homicide rate for every hundred thousand women. Elected as corpus research news on gender violence in ES, aired in 2013, in the newspapers A Gazeta and A Tribuna. Under no circumstances, we believe that this news helps to build social representations of gender violence from the presentation of victim and perpetrator stereotypes in society, the individualization of the problem of violence, this problem Association to less privileged social classes and presentation of crime of gender violence as a crime of passion. The study of this news comes as something complex, which not only participate in information, language problems, but also social, historical, cultural and cognitive, since the discursive analysis cannot be dissociated from the context of social actors and institutions involved in the production of news, and of these ideologies in the process. For this reason, we assume as theoretical basis of our research a multidisciplinary proposal: a Sociocognitive Theory from Teun A. van Dijk (1999a; 2011a; 2012; 2014b). In addition, we rely on the contributions of studies on gender and discourse from Cameron (1985, 1997), Wodak (1997), West, Lazar and Kramarae (2000), Fernández Díaz (2003), Lazar (1993, 2005, 2007), Magellan (2005; 2009), Heberle, Ostermann and Figueiredo (2006). Also we used the corpus linguistics program WordSmith Tools to perform quantitative analysis. The results of the analysis led us to the confirmation of the initial hypothesis: the discourse of news reinforces stereotypes victim and aggressor, typical of a patriarchal social structure, which is attributed to the victim or vices (alcohol and drugs) the responsibility of the violence suffered; moreover, gender violence is presented as an individual problem and associated to lower social classes; and, finally, the discourse of the news has much of crimes of gender violence as crimes of passion.